A feeling of not being alone - Patients' with COPD experiences of a group‐based self‐management education with a digital website: A qualitative study - Mia Berglund; Susanne Andersson; Anna Kjellsdotter (Wiley, 2024)
Abstract Aim To describe patients' with chronic obstructive pulmonary disease (COPD) experiences of group‐based self‐management education with a digital website. Design A qualitative approach with a phenomenologicalmethod. Patients participating in an earlier study, with self‐experience of COPD as a special competence, were involved as research partners at the design of this study. Methods Eleven individual and two group interviews with five participants in each group were conducted. Results Group‐based self‐management education with a digital website supports learning. Sharing experiences with others in similar situations creates security and reduces the feeling of being alone. Based on questions and discussion in the group, and through self‐reflection, general information is transformed into useful knowledge and understanding of one's own situation. COPD information on the website provides an opportunity to gain knowledge continuously based on needs that contributes to learning. This research has demonstrated that adapting learning activities to individual learning styles increases sustainability of learning. Sharing experiences reduces feelings of loneliness. It is therefore important to create spaces for sharing experiences and in‐depth reflection that support learning over time.